2016
DOI: 10.1177/0193945916647961
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Quality of Life in Patients With Primary and Secondary Lower Limb Lymphedema

Abstract: Patients with lower-limb lymphedema experience symptoms that may differ in intensity and distress. This mixed-methods study compares symptom intensity and distress and the impact of lymphedema on patients’ quality of life by primary and secondary (cancer and non-cancer) lymphedema groups. Individuals completed an online questionnaire (i.e., demographic form, Lymphedema Symptom Intensity and Distress Survey-Leg, and an open-ended question). Analyses included descriptive and inferential statistics (quantitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(72 citation statements)
references
References 29 publications
2
70
0
Order By: Relevance
“…There are a number of questionnaires specifically for lymphedema available internationally, but to date this is the only one that has been translated and culturally adapted for Brazil. 11,16,17 The Lymph-ICF-LL was used to assess physical, mental, and social abilities in relation to lymphedema. It does not classify patients, but provides a score which indicates greater health consequences from lymphedema the closer it approaches to 10.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are a number of questionnaires specifically for lymphedema available internationally, but to date this is the only one that has been translated and culturally adapted for Brazil. 11,16,17 The Lymph-ICF-LL was used to assess physical, mental, and social abilities in relation to lymphedema. It does not classify patients, but provides a score which indicates greater health consequences from lymphedema the closer it approaches to 10.…”
Section: Discussionmentioning
confidence: 99%
“…5,[10][11][12][13][14] Studies evaluating functionality and quality of life in lymphedema do so using assessment methods such as questionnaires, whether disease-specific or generic, and also using physical tests to identify and quantify issues related to the disease and its effects on the different domains of patients' lives. 11,12,[15][16][17][18] A review study conducted in 2013 18 with the objective of identifying questionnaires focused on lymphedema related the concepts they covered to concepts from the International Classification of Functioning, Disability and Health (ICF). The results showed that several different questionnaires are used to assess a range of aspects among patients with lymphedema.…”
Section: Introductionmentioning
confidence: 99%
“…Lymphovenous anastomosis can improve signs and symptoms but this is only valuable in early disease. Patients’ quality of life [, ] is profoundly effected by lymphoedema. Simple tasks we all take for granted can be extremely challenging for those with lymphoedema.…”
Section: Literaturementioning
confidence: 99%
“…Lymphedema is a disease that in the congenital (primary) and acquired (secondary) forms causes numerous problems in the individual life [1-3]. Despite of many attempts that have been accomplished in order to cure this disease, but no certain cure has been still mentioned for it.…”
Section: Introductionmentioning
confidence: 99%